2010
DOI: 10.1007/s12540-010-1213-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bending fatigue on the electrical resistance in metallic films on flexible substrates

Abstract: The increase of electrical resistance during the strain-controlled bending fatigue of 2 µm-thick inkjet-printed or vacuum deposited metallic films (Cu, Ag) on flexible substrates (BT: Bismaleimide Triazine, PI: Polyimide) was investigated. Electrical resistance increased with an increase in the number of fatigue cycles. The rate of increase in the electrical resistance of inkjet-printed Cu films was lower than that of thermally evaporated films. This phenomenon is attributable to the porous microstructure of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…The PEDOT:PSS thin film deposited on top of the flexible DBR showed an increment of its electrical resistance of about 15% after 1,000 bending cycles, with a curvature radius of 2.5 mm; whereas in the same stress conditions, the thin silver film showed an improvement of more than 100% (Figure 4). Such results confirm the superior flexibility of PEDOT:PSS with respect to metallic electrodes, as already reported in literature [15,27,28].…”
Section: Resultssupporting
confidence: 91%
“…The PEDOT:PSS thin film deposited on top of the flexible DBR showed an increment of its electrical resistance of about 15% after 1,000 bending cycles, with a curvature radius of 2.5 mm; whereas in the same stress conditions, the thin silver film showed an improvement of more than 100% (Figure 4). Such results confirm the superior flexibility of PEDOT:PSS with respect to metallic electrodes, as already reported in literature [15,27,28].…”
Section: Resultssupporting
confidence: 91%
“…Accumulation of the vacancies can then create vacancy clusters or voids with the progression of bending fatigue that results in extrusions at the top surface. High stress concentrations near the edges of protrusions can then initiate nucleation and propagation of micro‐cracks that cause a sharp increase in resistance of thin films . This fatigue failure mechanism for thin films was found to be the responsible failure mechanism in the case of Ag thin films in the report by Schwaiger et al…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, the difference in the increase in daisy chain resistance could plausibly be attributed to the number of hillocks formed in the interconnects since the number of hillocks found on copper interconnects was comparatively higher than the number of hillocks on aluminum and gold interconnects (Figures 7 and 9). Lee et al have observed that the formation of dislocations and vacancies in thin copper films during bending results in resistance increase [56]. Similar vacancies and dislocations plausibly formed underneath the hillocks could act as electron scattering centers thus increasing the daisy chain resistance.…”
Section: Optical Analysismentioning
confidence: 99%